AUV with Underwater Acoustic-WIFI Link Cooperative Control for Confined Waters - Meng ZHANG; Bowen WEI; Junhao JIN; Feng TONG; Fumin ZHANG (水下无人系统学报)
Autonomous undersea vehicle(AUV) generally adopts acoustic communication links for underwater control. However, in complex and confined waters such as coastal shoals, reservoirs, lakes, canals, and caves, complex multiple paths can seriously impact the performance of high-speed underwater acoustic communication, while the limited water depth of these environments makes wireless links a viable option. Therefore, a micro-sized AUV, SubseaBuddy-3, was developed that integrated both underwater acoustic and WIFI links for cooperative control. The underwater acoustic link adopted the low-speed spread-spectrum communication mode to ensure communication reliability under strong multipath conditions, while the high-speed WIFI link could work in shallow water, be used for pre-deployment function testing, and assist with the control and observation during retrieval. By coordinating the underwater acoustic and WIFI links based on working depths and data acquisition/transmission states, the system ensured reliable command and control, along with real-time/quasi-real-time underwater image transmission in confined waters. Additionally, the AUV was equipped with an inertial measurement unit(IMU) and a depth sensor for attitude and depth control. The effectiveness of the dual-link communication system for AUVs was validated by the pool experiment.